ECHOVIRUS TYPE 4 MENINGITIS AND RELATED FEBRILE ILLNESS: EPIDEMIOLOGIC STUDY OF AN OUTBREAK IN TWO ESKIMO COMMUNITIES IN 1970 - KAPLAN, GARY J.; BENDER, THOMAS R.; CLARK, PAUL S.; JONES, T. STEPHEN; SHERMAN, STEPHEN A.; NOBLE, GARY R.; TEGTMEIER, GARY E.; CHIN, T. D. Y. (Oxford University Press, 1972)
Kaplan, G. J., T. R. Bender (Ecological Investigations Program, 225 Eagle St., Anchorage, Alaska 99501), P. S. Clark, T. S. Jones, S. A. Sherman, G. R. Noble, G. E. Tegtmeier and T. D. Y. Chin. Echovirus type 4 meningitis and related febrile illness: epidemiologic study of an outbreak in two Eskimo communities in 1970. Am J Epidemiol 96: 74–85, 1972. Outbreaks of echovirus type 4 aseptic meningitis and related febrile illness involving 116 person in Kotzebue and 109 persons in Bethel, Alaska, occurred in the summer and fall of 1970. Virus isolation and/or fourfold rises in antibody titer were obtained in 23 cases in Kotzebue and in 36 cases in Bethel. In both villages, the illness was characterized by fever, headache, nausea, and vomiting. Stiff neck, photophobia, weakness, and lethargy were also common but rash was present in only two cases. In Kotzebue, a random survey of 55 households comprising 344 persons revealed an overall attack rate of 10%, with the highest age-specific attack rate in the 5- to 9-year age group. In Bethel, a survey of 24 households comprising 182 persons participating in an ongoing acute respiratory disease study revealed an overall attack rate of 27%, with similar age specific attack rates. Serologic studies showed that the proportion of Bethel family members having subclinical infections was higher than those with related febrile illness or aseptic meningitis. Previous echovirus 30 infection did not confer immunity against the development of echovirus 4 infection in either village. Cyclic variations in echovirus 4 and other echovirus types are discussed.